Analysis of Grab Transportation Services in Ciamis Regency, West Java, Indonesia - Adang Djatnika Effendi (UIN Sunan Gunung Djati, 2023)
Problems with customer satisfaction at PT. Grab Indonesia in Ciamis Regency, where certain customers are still dissatisfied with the services offered, served as the inspiration for this study. This may be affected by how well PT Grab Indonesia's drivers perform in the Ciamis Regency region. An estimated t value of 12.965 and a significance value of 0.0000.05 indicated that Tangible (Physical Evidence) has a substantial impact on customer satisfaction. With a t count of 1.101 and a significance value of 0.274>0.05, reliability does not significantly influence customer happiness. With a t count of 2.677 and a significance value of 0.0090.05, responsiveness has a favorable and substantial impact on consumer power. With a t count of -3.293 and a significance value of 0.001 to 0.05, assurance has a favorable and substantial impact on organizational commitment. With a t count of 4.668 and a significance value of 0.0000.05, Emphaty has a favorable and significant impact on customer satisfaction. As can be observed from the significant value of 0.00 0.05 and the computed F value of 66.765, which is higher than the F table, Service Quality characteristics such as tangible, reliability, responsiveness, assurance, and empathy jointly affect Customer Satisfaction. The tangible variable, or physical evidence, has the largest beta of all the variables, making it the variable that is most dominant when compared to other variables. The effect of service quality characteristics on customer satisfaction was found to be 78% Rsquare in this study, while the remaining 22% was influenced by other variables that were not examined.